The negative and detrimental effects of high fructose on the liver, with special reference to metabolic disorders - Mai BH (Dove Medical Press, 2019)
Brandon H Mai, Liang-Jun YanDepartment of Pharmaceutical Sciences, UNT System College of Pharmacy, University of North Texas Health Science Center, Fort Worth, TX 76107, USAAbstract: The increased consumption of fructose in the average diet through sweeteners such as high-fructose corn syrup (HFCS) and sucrose has resulted in negative outcomes in society through producing a considerable economic and medical burden on our healthcare system. Ingestion of fructose chronically has contributed to multiple health consequences, such as insulin resistance, obesity, liver disorders, and diabetes. Fructose metabolism starts with fructose phosphorylation by fructose kinase in the liver, and this process is not feedback regulated. Therefore, ingestion of high fructose can deplete ATP, increase uric acid production, and increase nucleotide turnover. This review focuses the discussion on the hepatic manifestations of high fructose-implicated liver metabolic disorders such as insulin resistance, obesity due to enhanced lipogenesis, non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), and type 2 diabetes. The detrimental effects of high fructose on the liver, contributed potentially by microbiome and leptin, were also discussed. The authors believe that, together with diet management, further studies focusing on disrupting or blocking fructose metabolism in the liver may help with designing novel strategies for prevention and treatment of fructose-induced chronic liver metabolic diseases.Keywords: fructose, liver, metabolic syndrome, non-alcoholic fatty liver disease, non-alcoholic steatohepatitis